2020
DOI: 10.1002/adem.202001016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation‐Resistant Environmental Barrier Coatings for Mo‐Based Alloys: A Review

Abstract: Molybdenum‐based materials offer high melting temperatures and promising mechanical properties; therefore, they are potential candidates for high‐temperature components, such as turbine blades. However, at temperatures above 700 °C, molybdenum suffers from severe pesting phenomenon, leading to decomposition of the component. Therefore, oxidation‐resistant environmental barrier coatings are crucial to prevent the material from degradation and to maintain its excellent mechanical properties at high temperatures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 114 publications
(261 reference statements)
0
6
0
Order By: Relevance
“…Additionally, it was observed that the HVOF coatings of Al0.3CrFeCoNiNb0.5 (see Figure 1d) and Al0.3CrFeCoNiMo0.75 (see Figure 1f) are characterized by a higher proportion of oxidized particles (gray lamellae in Figure 1d,f). It is well known from the literature that the elements Nb and Mo are susceptible to atmospheric oxidation [42,43]. Given this, the higher proportion of oxide lamellae in the Al0.3CrFeCo-NiNb0.5 and Al0.3CrFeCoNiMo0.75 HVOF coatings can be explained.…”
Section: Characterization Of the Initial Microstructurementioning
confidence: 94%
“…Additionally, it was observed that the HVOF coatings of Al0.3CrFeCoNiNb0.5 (see Figure 1d) and Al0.3CrFeCoNiMo0.75 (see Figure 1f) are characterized by a higher proportion of oxidized particles (gray lamellae in Figure 1d,f). It is well known from the literature that the elements Nb and Mo are susceptible to atmospheric oxidation [42,43]. Given this, the higher proportion of oxide lamellae in the Al0.3CrFeCo-NiNb0.5 and Al0.3CrFeCoNiMo0.75 HVOF coatings can be explained.…”
Section: Characterization Of the Initial Microstructurementioning
confidence: 94%
“…[40], and a specific overview dealing with poly(silazane)-based coatings for refractory metal-oxidation protection is given in ref. [41].…”
Section: Coatingsmentioning
confidence: 99%
“…Research on alloys based on refractory metals, such as molybdenum, is of active interest due to the possibility of manufacturing parts from them that operate at temperatures above 1300 • C. However, molybdenum undergoes severe destruction at temperatures above 730 • C [1]. The problem of increasing heat resistance is solved in several ways: by alloying alloys with elements that can form stable, protective films during oxidation [1][2][3][4], by applying protective coatings [5][6][7], or by a combined method. The most promising and realistic way to solve the heat resistance problem is using coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising and realistic way to solve the heat resistance problem is using coatings. The most common type of high-temperature protective coatings are coatings with the participation of silicon, the high heat resistance of which is explained by the ability to form a surface oxide film based on SiO 2 [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%